Evaluation of Anterior Segment Parameters in Pseudoexfoliative Glaucoma, Primary Angle-Closure Glaucoma, and Healthy Eyes - Nilgün Özkan Aksoy; Burçin Çakır; Emine Doğan; Gürsoy Alagöz (Türk Oftalmoloji Dergisi, 2018)
Objectives: To evaluate anterior segment parameters measured by dual Scheimpflug corneal topography in pseudoexfoliative glaucoma (PEXG), primary angle-closure glaucoma (PACG), and healthy eyes. Materials and Methods: One hundred forty-three eyes of 86 patients were included in this study. Forty-seven eyes of 38 patients with PEXG, 30 eyes of 15 patients with PACG, and 66 eyes of 33 healthy subjects were evaluated. Patients who underwent previous ophthalmic surgery and contact lens wearers were excluded. After full ophthalmological examination, mean central corneal thickness (CCT), white-to-white horizontal corneal diameter (WTW), pupillary diameter (PD), anterior chamber volume (ACV), anterior chamber depth (ACD), and mean anterior chamber angle were measured by dual Scheimpflug corneal topography and compared between the three groups. Statistical analyses were done using Statistical Package for Social Sciences for Windows 18.0 program. Results: No statistical difference was found in mean age or gender among the study groups (p>0.05). There were also no statistical differences in CCT, WTW, or PD among the groups (p=0.568, p=0.064, p=0.321, respectively). ACV, ACD, and mean anterior chamber angle values were significantly lower in the PACG group compared to the other groups (p=0.000 for all). There was no statistically significant difference in these measurements between the PEXG and normal eyes. Conclusion: ACV and depth and mean anterior chamber angle were statistically different (lower) in PACG when compared with PEXG and healthy eyes. Dual Scheimpflug corneal topography can be used as an objective method for the measurement of anterior segment parameters in glaucoma.